Australian Alleculinae: New Genera, New Combinations, and a Lectotype Designation (Coleoptera: Tenebrionidae) - Eric G. Matthews (Psyche: A Journal of Entomology)
Litopous baehri gen. et sp. nov. and Scaphinion clavatus gen. et sp. nov. are described. New combinations (previous genus in parentheses) are Aethyssius minor (Carter) (Tanychilus Newman), Homotrysis subopaca (Carter) (Metistete Pascoe), Metistete armata Carter (Homotrysis Pascoe), M. opaca (Carter) (Tanychilus), M. punctata (Carter) (Melaps Carter), and Nocar subfasciatus Carter (Taxes Champion). A lectotype and two paralectotypes are designated for Dimorphochilus diversicollis Borchmann which is removed from synonymy, and the genus is briefly discussed.